Management of Zenker and Hypopharyngeal Diverticula (Springer International Publishing, 2018)
This book will serve as an invaluable resource for surgeons and clinicians responsible for the evaluation and care of patients with Zenker's diverticula (ZD) and hypopharyngeal diverticula. The book reviews the surgical treatment approaches used historically as a context to a thorough discussion and presentation of newer, less invasive endoscopic approaches for therapy. The surgical techniques used with these endoscopic approaches, and the technological advances that have made them possible, is also presented in detail, along with the results, indications, limitations, and alternatives to these treatments. Expected clinical outcomes with these approaches are contrasted with alternative, more invasive surgical techniques that remain useful in select situations. Detailed information on these more invasive techniques are also presented along with more novel investigational treatment approaches including endoscopic therapy. Written by experts in the field of otolaryngology, speech language pathology, gastroenterology and radiology, Management of Zenker's and Hypopharyngeal Diverticula,will serve as an invaluable resource for surgeons, clinicians and students dealing with and learning about ZD and hypopharyngeal diverticula. The most up-to-date information is comprehensively offered to provide a primary source of clinical information for those caring for these patients. .